Preparation of Chitosan- CMC Blends and Studies on Thermal Properties. (2016) - Thomas, Sari; Soloman, P.A.; Rejini, V.O.
Abstract: Chitosan be a biopolymer, which is an amino polysaccharide resultant from the N-deacetylation of Chitin. It is an ordinary polymer because of the occurrence of degradable enzyme Chitosanase. Chitosan is blend with natural polymer CMC with glycerol and formaldehyde enhance the thermal stability. It is evident, that the weight loss (%) of Chitosan cross-linked with formaldehyde was greater compared with pure Chitosan. Degradation temperature of pure Chitosan is 120 °C. Optimum thermal stability was obtained at Chitosan cross linked with 0.2% formaldehyde was at 220 °C. Chitosan with excessive amount of cross linking agent results the formation of hydro gel. CMC cross linked with formaldehyde enhance the thermal stability compared with pure CMC. Degradation temperature of pure CMC is 240 °C. Optimum thermal stability was obtained at CMC cross linked with 0.4% formaldehyde is at 260 °C. Thermo gravimetric analysis was conducted to measure the weight loss of a standard solution of CS/CMC (99/1) and glycerol (2%) with different percentages of formaldehyde. Optimum thermal stability was obtained at a standard solution of CS/CMC blend (99/1) and glycerol (2%) with 0.4% formaldehyde was at 150 °C.